Morning exercise improves sleep quality in university students - Chahine, Krystel R.; Chahine, Nathalie R.; Nader, Moni (International Journal of Research in Medical Sciences, 2022)
Background: Although sleep is influenced by exercise, a proper management of physical activity’s time promotes the quality of sleep. The objective of this study was to evaluate, in university students, the effect of morning or evening physical exercise on sleep pattern, along with the dynamics of hormones controlling sleep quality. Methods: We recruited 92 healthy sedentary adolescents, 18-20 year-old, poor sleepers, with normal anthropometric characteristics and no musculoskeletal or neurological problems. They were randomly distributed into 3 groups: 34 subjects practicing morning physical activity, 28 subjects practicing evening physical activity, and 30 subjects remained sedentary. The quality of their sleep was assessed using the Spiegel validated questionnaire. Body temperature was recorded in the morning and evening, and saliva samples were collected. Saliva cortisol and melatonin levels were evaluated by ELISA. Results: The group practicing exercise in the morning experienced a better quality of sleep (71.4%) versus the one exercising in the evening (44.1%, p<0.05). In parallel, the levels of melatonin and cortisol significantly increased, at night and morning simultaneously, in participants exercising in the morning. Moreover, body temperature significantly decreased in participants that exercised in the morning compared to those who practiced evening exercise, or maintained a sedentary lifestyle (p<0.05). Conclusions: Our data indicate that morning physical activity exerts a positive impact on the sleep quality, probably by decreasing cortisol and increasing melatonin levels in the evening. We presume that morning activity may efficiently reduce the burden of sleep disorders, particularly those caused by COVID-19 lockdown.